Some Promising Control Measures for the Management of Meloidogyne spp. on "Gotukola" - Wijekoon, A.W.M.J.C.; Salim, N.; Ekanayake, H.M.R.K. (My University, 2001)
Cultivars of Centella asiatica were found to be infected by species of Melodogyne, a root knot nematode. Pot experiments under greenhouse were conducted to determine the effect of this nematode on the yield of these plants and attempts were also made to investigate suitable control measures. The use of resistant plants is a highly satisfactory method, which does not cause environmental pollution. In this study six cultivars of Centlla asiatica were tested for their susceptibility to this nematode. Both cultivars of high yielding type were found to be less resistant to Meloidogyne spp. whereas var. Mirigama was moderately resistant. Only one was found to be highly resistant among the types tested. The loss of yield due to nematode infection was considerable in both cultivars of high yielding type compared to others, and a 29% loss in the yield was observed in the most susceptible culitvar tested. Meloidogyne spp. were effectively controlled using compost. Application of soil: sand: compost in the proporation of 1:1:4 completely inhibited, and the same mixture used at 1: 1:2 satisfactorily inhibited the nematode population giving maximum yield of Centella asiatica under the conditions tested.
Keywords: Centella asiatica; Meloidogyne; Root knot nematode